Postpartum diet and its relation with anemia - Al-Araji , Laith Issa Yassin; Rosli , Mona Mohd; Wan Su, Kamaruzaman (2011)
Postpartum diet is important in ensuring the mother can heal and reach back to her optimal potential. Imbalance nutrient, less than the body requirement may lead to anemia which can then take a toll to the mother, her family and her relationship; which is the opposite of the objective of the diet restriction. The aim of this study is to identify the significant of cultural postpartum diet and its relation with anemia while its specific objectives are to determine social beliefs to the recovery of postpartum Malay women, to evaluate the relationship between postpartum diet taboos on anemia and to identify the percentages of postpartum Malay women who follow the traditional beliefs. Cross sectional study design with a semi-self-administered questionnaires and experimental study was used. The population of the study was Kuantans population that came to the Beserah Polyclinic and Jaya Gading Polyclinic. The Malay postpartum confinement phase is different from the other community. Malay postpartum mothers observed the postpartum dietary belief handed down by the elders while following advices from health care practitioners. The implication of this study is that postpartum poultry intake have relationship with the Hb level after childbirth while if the intake does not result in discomfort to the mother, the mother would consume it if she considered herself as high risk of achieving anemia.